Trauma Incidence and Emergency Medical Services in Malawi - World Bank (World Bank, Washington, DC, 2022)
This report provides insights into the current situation and overall burden of trauma and RTCs in Malawi, shares what we have learned about how to effectively run a digital trauma registry in a low-resource setting, and highlights lessons learned from the implementation of the EMS pilot.